(untitled) (Global Journal of Science Frontier Research, 2017)
Earthquakes cause widespread landslides more than other geotechnical hazards. In this study, the controlling factors of earthquake induced landslides are identified and evaluated for the major earthquakes with magnitude ≥ 6.6 that occurred between 1998 – 2015 worldwide. A quantitative technique of data analysis was applied to correlate controlling variables and landslides occurrence to draw their relationship determined by regression coefficient. Data was drawn from secondary sources; scientific and technical papers, technical reports, internet sites and relevant books on landslides. The analysis reveal that earthquake induced landslides spatial distribution has no correlation with earthquake magnitude and peak ground acceleration, but a weak positive correlation with respect to peak ground acceleration times shaking duration and Arias intensity. Earthquake induced landslides occurrence also show a strong correlation with regards to geology, fault type, slope angle and slope height. A negative correlation was established between earthquake induced landslides spatial distribution and the distance from the epicentre and surface rupture.